SOLVING THE PROBLEM OF LOGICAL OMNISCIENCE. - Dogramaci, Sinan (Philosophical Issues, 2018)
This paper looks at three ways of addressing probabilism's implausible requirement of logical omniscience. The first and most common strategy says it's okay to require an ideally rational person to be logically omniscient. I argue that this view is indefensible on any interpretation of 'ideally rational'. The second strategy says probabilism should be formulated not in terms of logically possible worlds but in terms of doxastically possible worlds, ways you think the world might be. I argue that, on the interpretation of this approach that lifts the requirement of certainty in all logical truths, the view becomes vacuous, issuing no requirements on rational believers at all. Finally, I develop and endorse a new solution to the problem. This view proposes dynamic norms for reasoning with credences. The solution is based on an old proposal of Ian Hacking's that says you're required to be sensitive to logical facts only when you know they are logical facts.